2018
DOI: 10.1111/bph.14132
|View full text |Cite
|
Sign up to set email alerts
|

Different contributions of chemokine N‐terminal features attest to a different ligand binding mode and a bias towards activation of ACKR3/CXCR7 compared with CXCR4 and CXCR3

Abstract: These results suggest a different interaction mechanism between this atypical receptor and its ligands and illustrate its strong propensity to activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 78 publications
(135 reference statements)
7
77
2
1
Order By: Relevance
“…Moreover, the authors suggest that arrestin binding to ACKR3 is not required for chemokine scavenging . The finding somewhat contrasts other observations where it was shown that CXCL11 and CXCL12 binding to ACKR3 enhances arrestin recruitment …”
Section: Introductioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Moreover, the authors suggest that arrestin binding to ACKR3 is not required for chemokine scavenging . The finding somewhat contrasts other observations where it was shown that CXCL11 and CXCL12 binding to ACKR3 enhances arrestin recruitment …”
Section: Introductioncontrasting
confidence: 57%
“…In their study, the authors used peptides derived from the N‐termini of CXCL11 and CXCL12, to show different binding and activation potencies depending of amino acid substitutions. However, contrarily to our chimeric chemokine, which has comparable affinity to ACKR3 as the natural ligands, the peptides have a markedly lower affinity (100–2000‐fold) for ACKR3 . It is conceivable and in line with radiolytic footprinting analysis of CXCL12:ACKR3 complexes, that both the N‐terminus and the body constitute together the high affinity binding to ACKR3 …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Improvement of chemokine‐derived short peptide affinity and potency by dimerization via a disulfide bridge at the first cysteine residues has previously been reported and suggested to be due, at least in part, to a mimicry effect of the first disulfide bridge present in the parental chemokines . Surprisingly, in the current study, dimerization of Mimokine SR (D) with C terminal cysteine or lysine linkers enhanced to the same extent the peptide interaction with CXCR4, suggesting that other effects might also be involved.…”
Section: Discussionmentioning
confidence: 39%
“…These studies led to the identification of a 21‐mer peptide derived from the N‐terminus of vCCL2 (vCCL2 (1–21) ) that displayed only modest CXCR4‐binding affinity and antiviral properties. We have recently identified vCCL2 and peptides derived from its N‐terminus as novel agonists of ACKR3 . In the current study, we exploited the high throughput screening capacity of the phage display technology to select Mimokines, vCCL2 (1–21) peptide‐based variants with enhanced CXCR4‐binding properties and selectivity.…”
Section: Introductionmentioning
confidence: 99%